Ground engineering proceedings of the conference organized by the Institution of Civil Engineers in London, 16 June 1970. (Institution of Civil Engineers, 1970)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in June 1970.